Assessment of Pentraxin 3 (PTX3) and Sclerostin (SOST) Levels in Serum of Patients with Chronic Kidney Disease (Medico Legal Update, 2021)
In the present study, 70 of patients were 35 males and 35 females were suffering from chronic kidneydisease, and 20 of control group. The samples were collected from Specialized Center for Diseases andKidney Transplant in AL-Sadder Medical City/Najaf Governorate/Iraq, during the period from July tillAugust, 2019. The ages of control and patients ranged 30 to 69 y old. The patients group was divided intosubgroup according to the age and gender, Patients without a complete medical record were excluded andthose with other diseases were excluded.The present study revealed a significant enhance (p0.05)in serum PTX3 and SOST levels there was a significant increase(p